Creación de un parque acuático para el mejoramiento de la infraestructura turística- hotelera en el sector Las Palmiras, ciudad de Quevedo, año 2019 - Torres Arrunátegui, Yomira Jazmín (2020)
In recent decades, much of the planet has experienced continued tourism growth and deep diversification, to become one of the fastest growing economic sectors. World tourism is closely linked to development and registers an increasing number of new destinations. Ecuador has a huge tourist potential to show the world. It is promoted by national and international tourism agencies. Each province and canton of Ecuador has its own characteristics, its natural charms, beautiful landscapes, culture and a unique folklore, which make it interesting to boost the tourism industry and thereby generate sources of work and boost the socioeconomic development of the sector. One of the problems that have the Quevedo canton is that despite having an excellent commercial activity and with the financing of entrepreneurs who have decided to invest in the city in view of their economic development, they lack a tourist offer that potentiates this sector despite the demand that currently exists. The creation of a water park that influences the improvement of tourism and hotel infrastructure in the Las Palmiras sector will help with the tourist offer of the canton, it will be a safe new attraction for people who want to have fun without the stress of traveling to other places that it causes them more expense and little guarantee of returning to the same site.